Evaluation of the Company‘s Capital Structure Determining Internal and External Factors in Baltic States during an Economic Shock - Pileckaitė, Odeta; Subačienė, Rasa (Buhalterinės apskaitos teorija ir praktika, 2023)
Capital structure’s formation and management decisions are one of the most important instruments to corporate financial management, enabling relevant business perspectives. The challenges of recent years and the increasing uncertainty in the economy make it necessary to assess how changes in capital structure are influenced by external and internal factors. Consequently, the purpose of the research is to evaluate the fluctuation trends in the capital structure of listed companies in the Baltic States and the correlation between the capital structure and internal and external factors. The object of the research is the financial data and correlation between the capital structure of listed companies in the Baltic States and external and internal factors. In order to achieve the research objective comparative, synthesis, regression, correlation and expert evaluation methods are applied. Furthermore, external financing of company investments generally decreased during the economic shock. Results of correlation analysis show that the capital structure of Baltic listed companies changes depending on the analysed period and the strongest impact on changes makes such internal factor as net profitability. On the basis of regression analysis it was determined that the leverage ratio was most affected by tax burden during the economic shock. This partly indicates that during the economic shock, the capital structure of Baltic listed companies was more influenced by external factors.
Keywords: capital structure; economic shock; external factors; internal factors; Baltic listed companies